2015
DOI: 10.1016/j.hrtlng.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Symptom clusters in patients presenting to the emergency department with possible acute coronary syndrome differ by sex, age, and discharge diagnosis

Abstract: Objectives To identify classes of individuals presenting to the ED for suspected ACS who shared similar symptoms and clinical characteristics. Background Describing symptom clusters in undiagnosed patients with suspected ACS is a novel and clinically relevant approach, reflecting real-world emergency department evaluation procedures Methods Symptoms were measured using a validated 13-item symptom checklist. Latent class analysis was used to describe symptom clusters. Results The sample of 874 was 37% fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 36 publications
6
29
1
4
Order By: Relevance
“…Another recent study that recruited patients from the emergency department found that women with an acute CHD event were likely to present without chest pain (Rosenfeld et al, 2015). Awareness of these prodromal and acute non-chest symptoms is critical for all clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study that recruited patients from the emergency department found that women with an acute CHD event were likely to present without chest pain (Rosenfeld et al, 2015). Awareness of these prodromal and acute non-chest symptoms is critical for all clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Ryan et al (2006) were the first to apply cluster analysis to symptoms of acute coronary syndrome, identifying five clusters of acute myocardial infarction symptoms. Acute coronary syndrome continues to be the focus of study in the cardiovascular cluster analysis nursing literature with multiple publications in the current decade (McSweeney, Cleves, Zhao, Lefler, & Yang, 2010; Riegel et al, 2010; Rosenfeld et al, 2015). …”
Section: Cluster Analysismentioning
confidence: 99%
“…The two primary approaches for optimizing ACS patient outcomes are to reduce treatment delay and to minimize total ischemic time, defined as time of symptom onset to reperfusion of culprit arteries (Hicks et al, 2015; O’Gara et al, 2013). ACS symptoms trigger patient care seeking behaviors and inform providers’ choice of diagnostic testing; yet symptoms are often ambiguous (Rosenfeld et al, 2015). If symptoms are neither identified nor recognized, patients may be at risk for increased prehospital delay, delayed diagnosis, and increased mortality and morbidity (Doggen et al, 2016; Fanaroff, Rymer, Goldstein, Simel, & Newby, 2015; Menees et al, 2013; O’Gara et al, 2013; Wu, Moser, Riegel, McKinley, & Doering, 2011).…”
Section: Introductionmentioning
confidence: 99%